2020
DOI: 10.1038/s41598-020-73324-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alzheimer’s disease and formalin fixation on the different mineralised-iron forms in the human brain

Abstract: Iron accumulation in the brain is a phenomenon common to many neurodegenerative diseases, perhaps most notably Alzheimer’s disease (AD). We present here magnetic analyses of post-mortem brain tissue of patients who had severe Alzheimer’s disease, and compare the results with those from healthy controls. Isothermal remanent magnetization experiments were performed to assess the extent to which different magnetic carriers are affected by AD pathology and formalin fixation. While Alzheimer’s brain material did no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…The concentrations of ferrihydrite-iron in the basal ganglia of our patient with aceruloplasminemia, could not be appropriately compared with results that had been previously obtained from the basal ganglia of healthy subjects and patients with neuroferritinopathy (29), due to substantial methodological differences between studies. The amount of ferrihydrite-iron in the temporal cortex of aceruloplasminemia, though, was six times higher than in healthy subjects and almost four times higher compared to patients with advanced Alzheimer’s disease that were measured under identical conditions (18, 34). Although these comparisons are limited to the temporal cortex, which is on average three times less rich in iron than the deep gray matter structures in aceruloplasminemia, they illustrates once more the severity of iron overload in aceruloplasminemia.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The concentrations of ferrihydrite-iron in the basal ganglia of our patient with aceruloplasminemia, could not be appropriately compared with results that had been previously obtained from the basal ganglia of healthy subjects and patients with neuroferritinopathy (29), due to substantial methodological differences between studies. The amount of ferrihydrite-iron in the temporal cortex of aceruloplasminemia, though, was six times higher than in healthy subjects and almost four times higher compared to patients with advanced Alzheimer’s disease that were measured under identical conditions (18, 34). Although these comparisons are limited to the temporal cortex, which is on average three times less rich in iron than the deep gray matter structures in aceruloplasminemia, they illustrates once more the severity of iron overload in aceruloplasminemia.…”
Section: Discussionmentioning
confidence: 66%
“…Absolute SIRM values detected at 100 K in aceruloplasminemia were approximately two orders of magnitude higher than those reported in healthy subjects, at room temperature (41), which suggests that also maghemite-iron levels may have increased as a result of iron overload in aceruloplasminemia. In addition, the concentration of maghemite-iron detected in the temporal cortex of aceruloplasminemia was almost twice that of healthy controls and advanced cases of Alzheimer’s disease that were measured under identical conditions (18, 34). In contrast to ferrihydrite-iron, the regional distribution of maghemite-iron in the aceruloplasminemia brain was not substantially different from that of healthy controls (41), with the cerebellar and brain stem nuclei being relatively rich in this magnetic carrier, although thalamic structures were not specifically investigated by previous studies (41).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The concentrations of ferrihydrite-iron in the basal ganglia of our patient with aceruloplasminemia could not be appropriately compared with results that had been previously obtained from the basal ganglia of healthy subjects and patients with neuroferritinopathy ( Hautot et al, 2007 ), due to substantial methodological differences between studies. The amount of ferrihydrite-iron in the temporal cortex of aceruloplasminemia, though, was six times higher than in healthy subjects and almost four times higher compared to patients with advanced Alzheimer’s disease that were measured under identical conditions, on average ( Bulk et al, 2018 , van der Weerd et al, 2020 ). Although these comparisons are limited to the temporal cortex, which is on average three times less rich in iron than the deep gray matter structures in aceruloplasminemia, they illustrate once more the severity of iron overload in the disease.…”
Section: Discussionmentioning
confidence: 68%
“…Reports of elevated postmortem tissue iron are inconsistent. Insufficient detection limits, small sample sizes in early studies, inaccuracies in the clinicopathological diagnosis of AD, and iron-depletion by fixatives may have contributed to this variance ( 88 , 253 , 254 ). A large recent study described that iron accumulation in the inferior temporal cortex could only be found in subjects both diagnosed clinically for AD and confirmed postmortem by standardized criteria ( 255 ).…”
Section: Ironmentioning
confidence: 99%